Estudo das propriedades ópticas de ormosils dopados com coloides de prata, cobre e prata:cobre - Orzari, Breno [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Optically active materials have attracted attention for technological applications because of the possibility of controlling absorption, reflection and transmission. Among these materials are photochromic materials, which are known by color change under electromagnetic radiation exposure (such as the case of ultraviolet (UV) radiation). Glasses containing silver ions have been reported as photochromic materials whose darkening and bleaching are due to the reduction or oxidation of these atoms. It is also reported that the insertion of copper ions intensifies photochromism in these materials. However, these types of glasses have some disadvantages, such as high temperatures to stabilize dopants in the glass matrix and the difficulty in preparing thin films. An alternative is the preparation of vitreous material from the sol-gel method, as is the case of organically modified silicates (ORMOSILs), which have been widely studied. Thus, the objective of this work was to study the optical properties of films of ORMOSILs doped with metal colloids and hybrid metallic colloidal systems, which were synthesized by sol-gel technique. For this work, silver and copper were chosen to be used as dopants, since the photochromic properties that their insertion can originate. The preparation of the samples was carried out using a hydrolyzed matrix of 3-glycidoxypropyltrimethoxysilane/ tetraethylorthosilicate (GPTS:TEOS) at a 4:1 molar ratio and the silver nitrate (AgNO3) and copper nitrate (Cu(NO3)2) were used as dopants. The doped solutions were deposited in microscope slides from the dip-coating technique. Characterizations were performed using ultraviolet and visible (UV-Vis) spectroscopy techniques. This technique allowed to identify alterations in the absorption band as a function of the time of exposure of the samples to UV radiation, as well as the life time and amplitudes of the photochromic effect presented by the films. From the results obtained it was...

Materiais opticamente ativos tem atraído atenção visando aplicações tecnológicas em razão da possibilidade de controlar absorção, reflexão e transmissão. Dentre esses materiais incluem-se os materiais fotocrômicos, que são conhecidos por apresentar mudança de cor sob exposição de radiação eletromagnética (como no caso da radiação ultravioleta (UV)). Vidros contendo íons de prata vem sendo relatados como materiais fotocrômicos cujos escurecimento e clareamento se dão pela redução ou oxidação desses átomos. É relatado também que a inserção de íons de cobre intensifica o fotocromismo nesses materiais. No entanto, estes tipos de vidros apresentam algumas desvantagens, tais como altas temperaturas para estabilizar dopantes na matriz vítrea e a dificuldade em preparar filmes finos. Uma alternativa é a preparação de material vítreo a partir do método sol-gel, como é o caso dos silicatos organicamente modificados (ORMOSILs), os quais vem sendo amplamente estudados. Assim, o objetivo deste trabalho foi estudar as propriedades ópticas de filmes de ORMOSILs dopados com coloides de metais e sistemas coloidais metálicos híbridos, que foram sintetizados via técnica sol-gel. Para este trabalho, foram escolhidos a prata e o cobre para serem utilizados como dopantes visto as propriedades fotocrômicas que sua inserção pode originar. A preparação das amostras foi realizada utilizando a matriz híbrida dos alcóxidos 3-glicidoxipropiltrimetoxisilano/ tetraetilortosilicato (GPTS:TEOS) na proporção molar de 4:1 e os sais nitrato de prata (AgNO3) e nitrato de cobre (Cu(NO3)2) foram utilizados como dopantes. As soluções dopadas foram depositadas em lâminas de microscópio a partir da técnica dip-coating. As caracterizações foram realizadas utilizando técnicas de espectroscopia na região do ultravioleta e do visível (UV-Vis). Tal técnica permitiu identificar alterações na banda de absorção em função do...
Keywords: Fisica otica; Fotocromismo; Coloides; Prata; Cobre; Ions metalicos; Processo sol-gel; Vidro; Silicatos; Absorção da luz